Analisis Implementasi Program Jam Belajar Mandiri (JBM) dalam Meningkatkan Kemandirian Belajar Peserta Didik di PKBM Terang Mulia Purwokerto Selatan - Tri Desy Rahmawati; Layla Marddliyah Marddliyah (STKIP PGRI SITUBONDO, 2026)
The Independent Learning Hours Program (JBM) is an educational initiative implemented at PKBM Terang Mulia, aimed at fostering independence, discipline, and responsibility among learners through structured yet flexible learning activities. This study aims to provide a detailed description of how JBM is designed, implemented, and how tutors facilitate the independent learning process. The research uses a descriptive qualitative method, with data collection through field observations, interviews with managers and tutors, and analysis of documentation such as the JBM book and weekly evaluation notes. The research results indicate that the implementation of JBM follows three main stages: setting learning targets, independent learning processes monitored by tutors, and regularly conducted reflection sessions. Tutors function as companions who assist learners in prioritizing their study without taking over the process. The findings show that JBM contributes to enhanced discipline, time management skills, and learners' independence in understanding the material. However, some challenges still arise, such as differences in learning abilities among students, a lack of supporting facilities, and some children's dependency on tutor guidance. Overall, JBM is deemed effective in supporting meaningful learning that aligns with the adaptive characteristics of nonformal education focused on the needs of the learners.